Simulações atomísticas em trifluoretos (REF3) e óxidos metálicos mistos (Re(TiTa)06) de terras-raras - Diniz, Eduardo Moraes (2006)
In this work static atomistic simulations were performed to investigate two systems: rare-earth trifluorides, REF3, with tysonite structure (RE = La, Ce, Pr and Nd) and rare-earth mixed metallic oxides, RE(TiTa)O6, with RE = Ce, Pr, Nd, Sm, Eu, Gd, Tb, Dy, Ho, Y, Er and Yb. In the rare-earth trifluorides was investigated the pressure induced structural phase transition identified by X-ray powder difraction in RE = La and Ce. The results shown that the crystalline structure is possibly tetragonal, in concordance with quantum mechanical calculations. For this, an interionic potential set that describes better the structural data of each compound and the physical observable was obtained. Besides, it was observed that critical pressure values were closed. The study involving the rare-earth mixed metallic oxides was focused in determining their bulk and structural properties. Thus, firstly a set of reliable interionic potentials was looked for to reproduce the crystalline structure and the physical observable, trough the investigation of three methodologies for obtaining interionic potentials, assuming the methodology that reproduces more reliable the dielectric constants. Furthermore, others bulk properties as lattice energy formation, elastic constants and bulk modulii were calculated. All then shown a rare-earth ionic radii dependence that revealed the morphotropic phase boundary between aeschynite and euxenite crystalline structures presented by these crystals.